Turismo, benchmarking e storytelling: um estudo sobre capacidades para gestão do turismo nas comunidades quilombolas "Negros do Riacho" e "Boa Vista dos Negros" no Seridó Potiguar - Farias, Mayara Ferreira de (2022)
The Community-Based Tourism has become the object of study of the research in evidence as an alternative for the implementation of tourist activity that values people, their history and culture, as well as that has been designed to promote better quality of life and responsible development. It is worth mentioning, in this perspective, that we chose to use storytelling because it is the “art of telling unforgettable stories”, which would allow us to understand about the history and experiences from the perception of the quilombolas of each studied community. Benchmarking, in turn, was chosen because it is considered a tool to search for the best management practices of an activity or entity that is used as a model for similar implementation, adapting to the reality of each location. Considering the time frame, it is worth noting that the field research was carried out in 2018 and 2019, in addition to remote interviews (online) in 2020 and 2021. It is also worth emphasizing that 2 (two) quilombola communities from the Seridó Region were chosen because they are the best known and most representative, namely: Quilombola Community Negros do Riacho (Currais Novos/RN) and Quilombola Community Boa Vista dos Negros (Parelhas/RN). Therefore, the general objective of this thesis was: to study the capacities for tourism management in the quilombola communities "Negros do Riacho" (Currais Novos/RN) and "Boa Vista dos Negros" (Parelhas/RN). It was, therefore, a research with a qualitative approach, with a descriptive and exploratory character. To this end, collection techniques were chosen for each specific objective listed, which have been: documentary research, bibliographic research, interview, Collective Subject Discourse (CSD), participant observation, Participatory Rapid Diagnosis (DRP) and, more significantly, storytelling and benchmarking. As analysis techniques, content analysis and discourse analysis were used. As main results, we can highlight that the sociocultural peculiarities, the experiences and the heritage (material and immaterial) make the quilombola communities in favorable spaces for a shared management and for the development of Community-Based Tourism in Seridó Potiguar. In addition, it was found that it is possible to use models (benchmarking) for the implementation of Locally Based Tourism activities with an emphasis on what was carried out in the city of Conde/PB, with emphasis on the Quilombola Ipiranga Community and Sítio Tambaba Camping (Tambaba Settlement, in Povoado Gurugi), realities that may reflect for the elaboration and direction of tourism development and management strategies in other traditional communities in the Seridó Region and in the state of Rio Grande do Norte. In the end, it can be concluded that storytelling and benchmarking are possible alternatives to be applied to the shared management of tourism through Community Based Tourism in Seridó Potiguar.